2019
DOI: 10.5897/jaerd2019.1073
|View full text |Cite
|
Sign up to set email alerts
|

Review on market re-orientation of extension services for value chain development in Borno State, Nigeria

Abstract: Hitherto the primary focus of agricultural extension in Borno State has been to ensure increasing agricultural production for food security. However, the current emphasis is on enhancing rural incomes through market reorientation. This change was necessitated by the realization that subsistence food production can no longer provide for a decent living and therefore increased engagement in commercial food production and markets has become a necessity and reality for the rural farmers. The paper explored the sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some of the factors responsible for unsatisfactory services are the small number of extension workers, their insufficient operational funding, their lack of transportation facilities and rare in-service training (MoA, 2018). Mwada et al (2019) reported that: "the concept of agricultural marketing extension may be new, however it could be regarded as the most neglected part of extension activities". In trying to show the importance of this type of extension, they also reported: "agricultural marketing extension is concerned with making the farmer understand and take advantage of market opportunities".…”
Section: Public Agricultural Extension In Jordanmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the factors responsible for unsatisfactory services are the small number of extension workers, their insufficient operational funding, their lack of transportation facilities and rare in-service training (MoA, 2018). Mwada et al (2019) reported that: "the concept of agricultural marketing extension may be new, however it could be regarded as the most neglected part of extension activities". In trying to show the importance of this type of extension, they also reported: "agricultural marketing extension is concerned with making the farmer understand and take advantage of market opportunities".…”
Section: Public Agricultural Extension In Jordanmentioning
confidence: 99%
“…The primary focus of agricultural extension today is on enhancing incomes through market-orientation (Christoplos, 2010). Market-oriented agricultural advisory services help farmers to overcome constraints related to a lack of adequate know-how and skills (Mwada et al, 2019).…”
Section: Public Agricultural Extension In Jordanmentioning
confidence: 99%